2015
DOI: 10.1586/14760584.2015.1082426
|View full text |Cite
|
Sign up to set email alerts
|

“Let there be light”: the role of vitamin D in the immune response to vaccines

Abstract: Vitamin D’s non-skeletal actions, including immunomodulatory role, have been increasingly recognized. Of significance, many immune cells are able to synthesize a biologically active form of vitamin D from circulating 25-(OH) D with subsequent intracrine actions, and the vitamin D receptor (VDR) is broadly distributed. In this review, we discuss vitamin D’s potent role in innate and adaptive immune responses and published studies evaluating the impact of serum vitamin D, vitamin D gene pathway polymorphisms or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 79 publications
1
49
0
Order By: Relevance
“…Micronutrients (vitamins A, D, and E and zinc). Vitamin D plays an important role in innate, humoral, and cellular immune responses (466). However, its role in influencing vaccine responses is not clear (466).…”
Section: Nutritional Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Micronutrients (vitamins A, D, and E and zinc). Vitamin D plays an important role in innate, humoral, and cellular immune responses (466). However, its role in influencing vaccine responses is not clear (466).…”
Section: Nutritional Factorsmentioning
confidence: 99%
“…Vitamin D plays an important role in innate, humoral, and cellular immune responses (466). However, its role in influencing vaccine responses is not clear (466). Most studies reporting on the effects of vitamin D on vaccine responses have investigated responses to TIV.…”
Section: Nutritional Factorsmentioning
confidence: 99%
“…Sadarangani et al [75,78] suggest that studying the impact of VDR-related polymorphism can provide further insight into the complex interactions in the context of vaccine-induced immune response.…”
Section: Does Vitamin D Affect the Immunogenicity Of Influenza Vacmentioning
confidence: 99%
“…Moreover, antigen-presenting cells as well as lymphocytes express the 1-α hydroxylase to convert serum 25-hydroxyvitamin D (25OHD) to its active form (1,25-dihydroxvitamine D), resulting in local intra- and paracrine actions. Studying the role of vitamin D on the functions of the immune system is an active field of research, and current knowledge indicates that vitamin D has various immunomodulatory effects, including actions on the innate immune system and orientating T-cellular immune responses towards a Th2 phenotype [3]. …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in mice, administration of vitamin D as an adjuvant during vaccination has shown to increase vaccine-induced immune responses (reviewed in [3]). In humans, several studies have shown that vitamin D level or supplementation does not influence the response to influenza vaccination, including in HIV-infected persons [713].…”
Section: Introductionmentioning
confidence: 99%